Pelatihan Pembuatan Pupuk Kompos Cair dari Sampah Organik di Desa Sentul, Kragilan, Serang-Banten - Setiawan, Lucky; Hibar, Ujang; Sairoh, Lisa; Maemunah, Maemunah; Muhitoh, Muhitoh; Subarjat, Ateng; Slamet, Muhammad (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2024)
National waste management is still a major problem, based on SIPSN data, it states that until July 24, 2024, the national waste accumulation was 31.9 million tons inputted from 290 districts and cities throughout Indonesia. Based on data from the Regional Innovation of the National Research and Innovation Agency (BRIN), it is known that 35.67% of the waste is unmanaged. One of the issues that is still hotly discussed in Serang Regency in the Development Planning Deliberation (Musrenbang) is the problem of waste which is still being debated, unmanaged and neglected. Until now, Serang Regency does not have an Integrated Waste Disposal Site or TPST. Therefore, the purpose of this community service is to apply appropriate technology in making liquid compost fertilizer from household waste materials which are then expected to enable the Sentul Village community to manage organic waste independently and sustainably and can reduce the volume of waste to TPS so that it can lighten the task of the Serang Regency government. The activity was carried out using two methods, namely: 1) Preparation and Q&A; 2) Education and simulation. The results of this Community Service are aimed at providing an understanding of the Community so that they can make their own compost fertilizer and can socialize it to other surrounding communities who have not received training. Therefore, the community service team provides a tool in the form of a starter kit that can be used as a guide for the Community to make fertilizer independently.